A benchmark study on reactive two-phase flow in porous media: part II - results and discussion - Ahusborde, Etienne; Amaziane, Brahim; de Hoop, Stephan; El Ossmani, Mustapha; Flauraud, Eric; Hamon, François P.; Kern, Michel; Socié, Adrien; Su, Danyang; Mayer, K. Ulrich; Tóth, Michal; Voskov, Denis (Computational geosciences, 2024)
This paper presents and discusses the results obtained by the participants to the benchmark described in de Hoop et al, Comput. Geosci. (2024). The benchmark uses a model for CO2 geological storage and focuses on the coupling between two-phase flow and geochemistry. Several test cases of various levels of difficulty are proposed, both in one and two spatial dimensions. Six teams participated in the benchmark, each with their own simulation code, though not all teams attempted all the cases. The codes used by the participants are described, and the results obtained on the various test cases are compared, as well as the performance of the codes. It is shown that the results obtained are widely consistent, giving a good level of confidence in the outcome of the benchmark. The general complexity of two-phase flow coupled with chemical reactions altering porous media means that some differences between the codes remain. Besides, from the convergence study, it is clear that the two-dimensional problem has a relatively high sensitivity to a spatial resolution which adds to the complexity.
Gesehen am 25.06.2024